HOW DO MARITIME ENGLISH COURSEBOOKS FACILITATE CADETS TO ACQUIRE PRAGMATIC COMPETENCE? FOCUS ON IMPERATIVE FORMS IN THE DIRECTIVE SPEECH ACT - Farida Indri Wijayanti (Universitas Sebelas Maret, 2021)
This article aims to describe the strategies of current maritime English coursebooks in presenting imperative forms in the speech act of directive. In this case, the strategies and pragmatic meanings of imperatives in two course books were investigated. The course books were also assessed to see if they were representative in terms of presenting imperatives to aid pragmatic competence development. Marlin’s coursebook showed multimodality strategies, but it was less sufficient in presenting imperatives since it only displayed them in emergency situation. On the other hand, IMO SMCP coursebook presented completely contexts in imperatives, but it only used text and dialog. Data was collected from 30 cadets with a multiple choice and DCT to measure their pragmatic competence after given the imperative materials. The results revealed that the cadets were able to perform imperatives almost completely appropriate in helpful context with pictures, but they still had problems to release imperatives in certain situations with text-only. Students’ attitudes toward the coursebook were they perceived that the coursebooks have already met the expectations in term of imperative forms. However, they saw helpful contexts with pictures like in Marlin coursebook were easier and better in improving their ability to produce imperatives.